The Incidental Finding of a Persistent Left Superior Vena Cava: Implications for Primary Care Providers—Case and Review - Loren Garrison Morgan; Jonathan Gardner; Joe Calkins (Case Reports in Medicine)
Persistent left superior vena cava (PLSVC) is the most common thoracic venous anomaly and is a persistent congenital remnant of the vena caval system from early cardiac development. Patients with congenital anomalous venous return are at increased risk of developing various cardiac arrhythmias, due to derangement of embryologic conductive tissue during the early development of the heart. Previously this discovery was commonly made during the placement of pacemakers or defibrillators for the treatment of the arrhythmias, when the operator encountered difficulty with proper lead deployment. However, in today’s world of various easily obtainable imaging modalities, PLSVC is being discovered more and more by primary care providers during routine testing or screening for other ailments. Given the known association between anomalous venous return and the propensity for cardiac arrhythmias, we review the embryology of PLSVC and the mechanisms by which it leads to conduction abnormalities. We also provide the practitioner with recommendations for certain baseline cardiac observations and suggestions for proper surveillance in hopes that better understanding will reduce unnecessary and potentially harmful testing, premature subspecialty referral, and unneeded patient anxiety.